Influence of gradation using local aggregate on porous asphalt to enhance stormwater absorption. Issue 1 (January 2021) - Sihombing, A V R; Utami, R; Somantri, A K
Abstract: Porous asphalt is one of the pavement technologies that have a large void in the mix and enables water flows through the pavement structure. Due to its porous characteristic, strength and stability of porous asphalt are lower than normal asphalt mix caused by coarse aggregate domination in mixture leads. Selection of aggregate and gradation highly affected desired porous asphalt characteristics, so that research is needed to understand the performance of porous asphalt using local material based on permeability characteristic, cantabro loss and marshall characteristic with several aggregate gradations from several countries. The method of this research would be a laboratory-scaled experiment. Materials for this research were asphalt pen 60/70 and local aggregate from Majalengka (M) with gradation variation from Japan (J), Australia (A), and Indonesian (I), then designed to obtain a porous asphalt namely MJ, MA, and MI. Permeability test showed lower value for every mixture with the highest permeability coefficient is on MI with 4.64 × 10 −5 cm/s. Cantabro loss gave the lowest value on MI with 20.45%. By permeability and cantabro loss, porous asphalt mixture with aggregate from Majalengka with Indonesian grading is the best one to represent environmentally friendly mixture and enhance stormwater absorption.